AB1415-HPR Differences on pain and structural anormalities between patients with rheumatoid arthritis and those with inespecific foot pain: cross sectional study. (12th June 2018) - Gijon-Nogueron, G; Reinoso-Cobo, A.; Ortega-Avila, A.B.; Caliz, R.
Abstract : Background: The presence of foot pain and deformity is ubiquitous in Rheumatoid Arthritis (RA). Epidemiological studies consistently suggest a prevalence of foot pain of 90%. 1 Weight gain, high levels of fatigue and deformities such us hallux valgus and metatarsus primus varus, are very frequent too. 2 Objectives: The aim of this study was to analyse pain levels and structural anormalities among subjects with foot pain and patients with RA. Methods: A sample comprised of 40 subjects was studied. Participants were recruited from a private podiatry clinic and from the Department of Rheumatology (Granada, Spain). The inclusion criteria were subjects with RA with a duration of at least 10 years according to the American Rheumatism Association criteria for RA, while patients with foot pain seeking podiatry services from April 2017 to January 2018 were used as control group. Outcome measures were as follows: foot pain, activity limitation, disability and foot health status by Foot Function Index questionnaire 3 and Hallux Valgus by Manchester Hallux Valgus Scale. 4 Results: As shown in Table 1, we found statistical significant differences for the pain scale(p>0.001) and in total score(p>0.001) in the FFI scale between AR group and the control group, but not between group in the Manchester Hallux Scale (p=0.986) Conclusions: We found higher levels of pain in subjects with RA compared to the control group. Furthermore, although there are clinical differences subjects with RA and with foot pain, we can not conclude strongly that RA increases the possibility of having deformities such as Hallux Valgus. References: [1] De Mits S, Mielants H, De Clercq D, et al. Quantitative assessment of foot structure in rheumatoid arthritis by a foot digitizer: Detection of deformities even in the absence of erosions. Arthritis Care Res2012;64:1641–8. doi:10.1002/acr.21794 [2] Helliwell P, Reay N, Gilworth G, et al. Development of a foot impact scale for rheumatoid arthritis. Arthritis Care Res2005;53: 418–22. doi:10.1002/art.21176 [3] Paez-Moguer J, Budiman-Mak E, Cuesta-Vargas AI. Cross-cultural adaptation and validation of the Foot Function Index to Spanish. Foot Ankle Surg2014;20:34–9. doi:10.1016/j.fas.2013.09.005 [4] Garrow AP, Papageorgiou A, Silman AJ, et al. The Grading of Hallux Valgus: Manchester Scale. J Am Podiatr Med Assoc2001;91:74–8.http://www.japmaonline.org/doi/abs/10.7547/87507315-91-2-74 Disclosure of Interest: None declared